1991
DOI: 10.1002/bjs.1800780512
|View full text |Cite
|
Sign up to set email alerts
|

Risks of leaving the gallbladder in situ after endoscopic sphincterotomy for bile duct stones

Abstract: There is controversy concerning the subsequent clinical course of patients whose gallbladder is left in situ following successful endoscopic removal of stones from their common bile ducts. A total of 191 patients (median age 76 years) were reviewed between 12 and 100 months (mean 38 months) after endoscopic sphincterotomy. Ten patients (5.2 per cent) had symptoms requiring cholecystectomy which was uneventful, nine in the first year. Cholangitis at presentation or failure to fill the gallbladder by endoscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 17 publications
2
39
0
1
Order By: Relevance
“…Some studies have suggested the effectiveness of endoscopic biliary sphincterotomy in these circumstances in preventing further episodes of acute biliary pancreatitis. These uncontrolled case series mostly suggest a reduction in the frequency of attacks of pancreatitis, although recurrent bile duct stones or acute cholecystitis may still be a problem in the future (255)(256)(257)(258)(259)(260)(261)(262)(263)(264). Before considering an empiric biliary sphincterotomy for recurrent pancreatitis with or without abnormal liver function tests, the clinician must be aware of the possibility of an alternative etiology, such as sphincter of Oddi dysfunction, especially in women, young or middleaged patients, and patients who are postcholecystectomy, or do not have clearly documented gallstone disease.…”
Section: Treatment Guideline Vii: Role Of Ercp and Biliary Sphincteromentioning
confidence: 99%
“…Some studies have suggested the effectiveness of endoscopic biliary sphincterotomy in these circumstances in preventing further episodes of acute biliary pancreatitis. These uncontrolled case series mostly suggest a reduction in the frequency of attacks of pancreatitis, although recurrent bile duct stones or acute cholecystitis may still be a problem in the future (255)(256)(257)(258)(259)(260)(261)(262)(263)(264). Before considering an empiric biliary sphincterotomy for recurrent pancreatitis with or without abnormal liver function tests, the clinician must be aware of the possibility of an alternative etiology, such as sphincter of Oddi dysfunction, especially in women, young or middleaged patients, and patients who are postcholecystectomy, or do not have clearly documented gallstone disease.…”
Section: Treatment Guideline Vii: Role Of Ercp and Biliary Sphincteromentioning
confidence: 99%
“…[1][2][3] Endoscopic stone extraction is successful in over 96% of patients [3][4][5] with a low procedure-related morbidity (5.8%) and mortality (0.2%). 3 Subsequent laparoscopic cholecystectomy (LC) is the standard treatment in those patients with concomitant gall-bladder stones.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have advocated a wait-and-see policy after ES for these patients because only an estimated 10% of them experience recurrent biliary symptoms in retrospective and nonrandomized studies [4][5][6][7][8]. However, in two prospective randomized trials, up to 47% of the patients presented with recurrent biliary symptoms after a wait-and-see policy, and the cumulative risk for death was 21% within 5 years (vs 5.8% for patients allocated to planned cholecystectomy) [9,10].…”
mentioning
confidence: 99%